BIMBINGAN KONSELING DAN KESUKSESAN BELAJAR - Basri, Basri (JURNAL TARBAWIYAH, 2014)
Guidance and counseling is given to a person in order to solve problems. Includes personal guidance counseling, social counseling, tutoring, and career guidance. Guidance and counseling support the achievement of the purpose of education and teaching in schools, this activity is done through service orientation , information services, tutoring service. Tutoring services necessary for the development of the personality and abilities of learners occurs optimally.Success in learning is largely determined by the ability and perseverance are conducted continuously. Guidance and counseling enables students to develop self-respect to attitude and good study habits, so that individuals can solve problems. Then guidance counseling in schools when done well can deliver students achieve success in learning. Keywords: Guidance , Counselling and Learning Success